EVALUASI KAPASITAS PENAMPANG KOLOM BETON BERTULANG MENGGUNAKAN DIAGRAM INTERAKSI (12 - 18) - Agus Subrianto; Puryanto Puryanto; Fadhila Firdausa (PILAR, 2020)
ABSTRACT This article discusses the rapid evaluation of the cross-section capacity of reinforced concrete columns which bears a combination of axial loads and two-way bending. The model under review is a 3-storey building that uses uniform column sizes. The structure of the building is analyzed using a computer-aided program to obtain internal forces. Interaction diagrams of several cross-section configurations are made to help check the working axial and flexural forces. By looking at the distribution of the combination of axial and flexural forces acting on the interaction diagram plot, it can be determined whether a cross section is efficient enough to be used in columns throughout the building. The results of the analysis show that the columns commonly used in shophouses are still safe in carrying out a combination of axial and flexible loads that work due to the influence of gravity loads. Keywords : column design, reinforced concrete, axial bending moment combination, section capacity, interaction diagram ABSTRAK Artikel ini membahas tentang evaluasi cepat kapasitas penampang kolom beton bertulang yang memikul kombinasi beban aksial dan lentur dua arah. Model yang ditinjau adalah bangunan ruko 3 lantai yang menggunakan ukuran kolom seragam. Struktur bangunan dianalisis menggunakan program bantu komputer untuk mendapatkan gaya-gaya dalam.  Diagram interaksi dari beberapa konfigurasi penampang dibuat untuk membantu melakukan pengecekan gaya aksial dan lentur yang bekerja.  Dengan melihat distribusi kombinasi gaya aksial dan lentur yang bekerja terhadap plot diagram interaksi, dapat ditentukan apakah suatu penampang cukup efisien untuk digunakan pada kolom di seluruh bangunan. Hasil analisis menunjukkan bahwa kolom yang biasa digunakan pada bangunan ruko masih aman dalam memikul kombinasi beban aksial dan lentur yang bekerja akibat pengaruh beban gravitasi. Kata kunci : disain kolom, beton bertulang, kombinasi lentur aksial, kapasitas penampang, diagram interaksi.